HANDGRIP STRENGTH AND DASH EATING BEHAVIOR IS RELATED TO HIGHER BLOOD PRESSURE ON PRE-ELDERLY AND ELDERLY IN YOGYAKARTA - Fayasari, Adhila; Febri Nilansari, Anis; Juang Bertorio, Margala (Universitas Airlangga, 2025)
Handgrip strength (HGS) reflects muscle health and is linked to hypertension, yet its relationship with blood pressure (BP) in older adults is underexplored. DASH dietary patterns, crucial for BP management, may provide further insights into this connection. This study aims to examine the association between HGS and DASH eating behavior with blood pressure in pre-elderly and elderly populations. A cross-sectional study was conducted on pre-elderly and elderly outpatient at Wirosaban Hospital, Yogyakarta in July to August 2024. HGS was measured using a hand dynamometer, while BP was recorded using a standard sphygmomanometer. Adherence to DASH were measured by 24-hour food recall and then categorized by questionnaire of DASH eating behavior. Data were analyzed by correlation and multiple regression, with α 5%. Hypertension was found in about 68.8% of subjects. Subjects who have lower HGS were about 68.8% and 81.7% of low category of DASH eating behavior. Participants with lower HGS had notably higher systolic and diastolic BP compared to those with higher HGS. Stratification analysis revealed that there were no significant association between HGS and high blood pressure both in elderly and pre-elderly (p 0.063 and p 1.000). In the other hand, low DASH eating behavior was significantly related to higher blood pressure in pre-elderly group (p 0.031). Reduced HGS is likely linked to higher BP in the elderly. Maintaining DASH-like diet adherence and muscle strength may be crucial in mitigating hypertension risk and comorbidity in older adults.